(untitled) - Nelson, Carl A. (New York, 2009)
Doing business across national borders is more profitable than ever. In the exhaustively revised fourth edition, Import/Export provides step-by-step guidance to show you how to take part in the booming world economy.
Keywords: International trade,Exports,Imports